Mechanism, Implementation, and Challenges in Independent Campus Education Policy in Indonesia - Deding Ishak (GoAcademica Research & Publishing, 2021)
The Independent Learning-Independent Campus Policy was issued by the Minister of Education and Culture of the Republic of Indonesia, Nadiem Anwar Makarim. The policy aims to improve the competence of graduates, both soft skills and hard skills, to be more prepared and relevant to the needs of the times, to prepare graduates as future leaders of the nation with excellent and personalities.